Mineral contents and nutritive values of the pomaces of commercial Turkish grape (Vitis vinifera L.) varieties - Sagdic, O.; Ozturk, I.; Yetim, H.; Kayacier, A.; Dogan, M. (CODON PUBLICATIONS, 2014)
Many by-products from food industries including grape pomace are generally used as animal feed or fertilisers. Grape pomace is considered as a valuable by-product for oil extraction, phenolics, tocopherols and antibacterial agents. Actually, the waste products could provide supplements for the food and drug industry. Our objective was to determine details of the nutritive values of grape pomaces of five commercial Turkish grape varieties to consider possible applications in the food and feed industry. In this study, some chemical properties and minerals contents, namely potassium (K), calcium (Ca), magnesium (Mg), sodium (Na), phosphorus (P), iron (Fe), zinc, copper, selenium, cobalt, chrome, lead and cadmium, of the grape pomaces were investigated. The results indicated that grape pomaces were generally acidic in nature with pH values of 3.82-4.30. Pomace is usually poor in sugar content and the variety of grape significantly affects the sugar content of the pomaces. Crude fibre was the major constituent of the grape pomace and ranged between 53.20 and 67.50%. Mineral analyses also showed that pomace samples had high K, Ca, Mg, Na, P and Fe contents. Consequently, the pomace samples of the grape varieties could be considered functional foods with high biological values.
Keywords: grape pomace; mineral content; nutritive value; Food Science & Technology